Tissue culture of root and tuber crops at IITA - Ng, S.Y.C. (1992)
At IITA, tissue culture methods, such as meristem, shoot-tip, and node-cutting cultures, are used routinely to eliminate virus infection from improved clones of cassava and yam and for micropropagating cassava, yam, sweet potato, and cocoyams. Virus-tested improved clones of cassava, yam, and sweet potato have been distributed to national programmes for evaluation and testing. The clonal germplasm is conserved by the in vitro reduced growth storage method; plantlets can be kept in the same tube for 1-2 years. An embryo culture technique for germinating mature embryos of Manihot species and immature embryos of cassava is being developed. Somatic embryos have been obtained in vitro from young cassava leaf material cultured in a medium containing picloram. Anther and unpollinated ovary culture of cassava, aimed at producing haploid plants, is under investigation. In vitro microtuber production of yams is an alternative that could aid international distribution of virus-tested clonal materials. The dormancy and uniform germination of microtubers need to be investigated.